Altered Function and Expression of ABC Transporters at the Blood–Brain Barrier and Increased Brain Distribution of Phenobarbital in Acute Liver Failure Mice - Liu, Li; Miao, Mingxing; Chen, Yang; Wang, Zhongjian; Sun, Binbin; Liu, Xiaodong (Frontiers in Pharmacology, 2018)
This study investigated alterations in function and expression of P-glycoprotein (P-GP), breast cancer resistance protein (BCRP) and multidrug resistance-associated protein 2 (MRP2) at the blood-brain barrier (BBB) of acute liver failure (ALF) mice and its clinical significance. ALF mice were developed using intraperitoneal injection of thioacetamide. P-GP, BCRP and MRP2 functions were determined by measuring the ratios of brain-to-plasma concentration of rhodamine 123, prazosin and dinitrophenyl-S-glutathione, respectively. The mRNA and proteins expression levels of P-GP, BCRP and MRP2 were evaluated with QT-PCR and western blot, respectively. MDCK-MDR1 and HCMEC/D3 cells were used to document the effects of the abnormally altered components in serum of ALF mice on the function and expression of P-GP. The clinical significance of alteration in P-GP function and expression was investigated by determining the distribution of the P-GP substrate phenobarbital (60mg/kg, intravenous administration) in the brain and loss of righting reflex (LORR) induced by the drug (100 mg/kg). The results showed that ALF significantly downregulated the function and expression of both P-GP and BCRP, but increased the function and expression of MRP2 in the brain of mice. Cell study showed that increased chenodeoxycholic acid may be a reason behind the downregulated P-GP function and expression. Compared with control mice, ALF mice showed a significantly higher brain concentration of phenobarbital and higher brain-to-plasma concentration ratios. In accordance, ALF mice showed a significantly larger duration of LORR and shorter latency time of LORR by phenobarbital, inferring the enhanced pharmacological effect of phenobarbital on the central nervous system. In conclusion, the function and expression of P-GP and BCRP decreased, while the function and expression of MRP2 increased in the brain of ALF mice. The attenuated function and expression of P-GP at the BBB might enhance phenobarbital distribution in the brain and increase phenobarbital efficacy on the central nervous system of ALF mice.